The second letter to the Corinthians - Seifrid, Mark A. (Pillar New Testament commentary., 2014)
The question that Paul set before the ancient church in Corinth -- Do you not recognize that Jesus Christ is in and among you? (2 Cor 13:5) -- remains a critical question for the church today. This commentary by Mark Seifrid seeks to hear Paul's message afresh and communicate it to our time. Seifrid offers a unified reading of 2 Corinthians, which has often been regarded as a composite of excerpts and fragments. He argues that Paul's message is directed at the practical atheism of the Corinthian church -- the hidden heresy that assumes God's saving work in the world may be measured by outward standards of success and achievement. Like all of the Pillar volumes, Seifrid's commentary on 2 Corinthians offers careful grammatical analysis and exegesis with clear pastoral application.